Varietal characteristics of cassava: farmers' perceptions and preferences in semiarid zone of west Africa - Kormawa, P.; Tshiunza, M.; Dixon, A.; Udo, E.; Okoruwa, V. (International Institute of Tropical Agriculture, 2003)
The study examines and models Farmers' perceptions and preferences of cassava· varietal characteristics vis-i-vis the decision ' to adopt cassava cultivars in their fields. The paper is built on the concept of the effect of technology-specific factors on adoption. By way of threshold decision modelling for each of the countries considered, the results reveal different scenario. Based on the varietal characteristics considered, environmental resistance quality (ERQ), high-yielding quality (HYQ), early maturing qualities (EMQ), leaf quality (LQ), inground storability quality (lSQ) and taste quality (TQ) have declining importance in the order of Iisting. As such, environmental resistance quality appears a major varietal characteristic that the farmers perceived and preferred for cultivating any cassava cultivar in the zone. The results, therefore, reinforce the relative importance of varietal characteristics in the choice and preference of cassava cultivars by farmers; it is, therefore, imperative for breeders to develop cultivars that will be acceptable to the farmers considering their level of preference and perceptions.